2014
DOI: 10.1016/j.msea.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Brittle-to-ductile transitions and its relation to the deformability of cementite in fully pearlitic steels

Abstract: Temperature dependence of absorbed impact energy in fully pearlitic steels was investigated. Two-step brittle-to-ductile transitions were observed. The value of the activation energy associated with the first transition is comparable to that of low carbon ferritic steels, indicating that the first transition is the brittle-toductile transition of ferrite phase in pearlitic steels. It suggests that the first transition is controlled by the dislocation glide in ferrite. The value of the activation energy associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Therefore, the wear process is supposed to be mainly two-body wear, so adhesive wear would be dominant and contribute to the considerable wear rate. Furthermore, at such an extremely low temperature, the ductility of steel will drop sharply to a fairly low level, producing what is called black brittleness in materials science [41][42][43]. During continuous sliding, the pins and discs are locally subjected to strong adhesive wear caused by micro cold welding, in which materials are temporarily transferred between the pins and discs.…”
Section: Discussion Of Wear At 3°cmentioning
confidence: 99%
“…Therefore, the wear process is supposed to be mainly two-body wear, so adhesive wear would be dominant and contribute to the considerable wear rate. Furthermore, at such an extremely low temperature, the ductility of steel will drop sharply to a fairly low level, producing what is called black brittleness in materials science [41][42][43]. During continuous sliding, the pins and discs are locally subjected to strong adhesive wear caused by micro cold welding, in which materials are temporarily transferred between the pins and discs.…”
Section: Discussion Of Wear At 3°cmentioning
confidence: 99%
“…The absorbed energy in this study decreases from 1 270 to 630 kJ/m 2 between 323 and 253 K. More- over, between 253 and 193 K, the energy decreases gradually from 630 to 530 kJ/m 2 . Finally, the energy transition appears clearly from 193 to 173 K. The DBT in this study is observed to occur with two steps, and there is a "middle shelf " 19) between the upper and lower shelf. Moreover, the width of the middle shelf range is over 60 K. We call the transition from the upper shelf to the middle shelf as "first transition" and the transition from the middle shelf to the lower shelf as "second transition."…”
Section: Impact Energymentioning
confidence: 48%
“…This model indicated the important factors that affect the relation shown in Fig. 14: the properties of structures in steel, 9,11,21) strain rate, 19) specimen thickness, 13) and shape of the notch. 13) However, the evidence for the model in this study is not sufficient.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous study, 10) we had investigated the ductileto-brittle transition (DBT) with decreasing temperature in ferrite + pearlite DP structural steel sheets using a Charpy impact test with sub-size specimens. The absorbed energy showed a two-step DBT behavior with decreasing temperature 11) and the transition curve showed a clear "middle shelf" (MS) between the upper shelf (US) and lower shelf (LS). In the MS, the absorbed energy remained at the middle level, and the fracture surface (FS) was found to be a cleavage-like surface with a few dimples.…”
Section: Introductionmentioning
confidence: 99%